Metal pollution assessment of surface water from the abandoned Pb mine Zaida, high Moulouya-Morocco. Issue 4 (3rd July 2020) - Bouzekri, Siham; El Hachimi, Moulay Laarabi; Kara, Kaoutar; El Mahi, Mohammed; Lotfi, El Mostapha
ABSTRACT: The purpose of this study is to evaluate the metal (As, Cd, Pb, Zn and Cu) pollution of surface water in a mining environment. To achieve this, water samples were taken from the Moulouya River, Ansegmir tributary and Hassan II Dam located downstream of the abandoned Pb mine. Which allowed to conduct a comprehensive physicochemical analysis. The results showed high metal concentrations in most sites. In fact, the levels of arsenic, cadmium, copper and lead are much higher than the specific values set by the World Health Organization for drinking water. While, cadmium exceeds the Moroccan irrigation standards at all studied sites. However, the correlation results showed a high correlation among Cd/As and Cu/Zn, but no correlation recorded between Pb and other metals, which can be explained by the special source of Pb 'the tailings'.